PENGEMBANGAN MEDIA INTERAKTIF BERBASIS PBL UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA FASE B - Helsa Qaira Sukmarani; Rosiana Mufliva; Diki Riyadi; Isna Soffi Aristin Rohiman (PT. Jurnal Center Indonesia Publisher, 2025)
Problem-solving ability is a skill that every individual must possess. Mathematical problem-solving is one of the skills that must be mastered in everyday life. This research aims to develop interactive learning media based on PBL to enhance students' mathematical problem-solving abilities. This research uses the Design and Development (D&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collection technique in this study used a questionnaire with a Likert scale. The research results indicate that the PBL-based interactive media is suitable for use, with validation from subject matter experts at 97.2%, media experts at 97.6%, and product trials at 87.5%. The improvement in problem-solving skills was also measured through the N-Gain test, with an N-Gain result of 1, indicating a high criterion. The improvement in students' mathematical problem-solving skills increased after using PBL-based interactive media. This demonstrates the importance of media in delivering education. Media designed according to students' needs effectively and efficiently can enhance students' interest, motivation, and understanding in learning.